An Investigation of Polymorphism on the FASN, SCD1, and SLC27A3 Genes in Sheep - Ali Osman Turgut; Erman Gülendağ; Mürsel Küçük; Davut Koca; Adnan Ayan; Mehmet Eroğlu; Muhammed Furkan Önen (Turkish Journal of Agriculture: Food Science and Technology)
Milk traits of sheep are affected by many environmental and genetic factors. These traits are quantitative traits and are determined by many genes. This study aimed to investigate polymorphisms of milk-related Fatty-acid synthase (FASN), Stearoyl-CoA desaturase (SCD1), and solute carrier 27A3 (SLC27A3) genes in cross-bred Hamdani sheep. Blood samples were collected from 100 healthy cross-bred Hamdani ewes from the jugular vein into K3-EDTA-containing tubes. Genomic DNA was extracted using a commercial DNA isolation kit. PCR products of FASN (275 bp), SCD1 (225 bp), SLC27A3-P1 (341 bp), and SLC27A3-P2 (319 bp) were subjected to restriction fragment length polymorphism (RFLP) analysis using SSil (AciI), Cfr13I, AluI, and Hpy188III the restriction enzyme, respectively. However, all gene regions were found to be monomorphic. In the study, only TT, AA, AA, and GG genotypes were detected for FASN, SCD1, SLC27A3-P1, and SLC27A3-P2, respectively. Allele and genotype frequencies were 1.00 for all genotypes and alleles. Although this study did not reveal favorable genotypes in FASN, SCD1, and SLC27A3 genes that can be used for milk traits, more comprehensive studies with larger sample sizes should be conducted to investigate polymorphisms in cross-bred Hamdani sheep.